Comparing ESG disclosure standards and firm value: Mediating role of credit-based loan loss provision in Indonesian banking - Marpaung, Netti Natarida; Wahyudi, Sugeng; Pangestuti, Irene Rini Demi (Edelweiss Applied Science and Technology, 2025)
This study investigates how different ESG disclosure standards influence firm value in the Indonesian banking sector, with a focus on the mediating role of Credit-based Loan Loss Provision (CLLP) as a proxy for credit risk governance. Using unbalanced panel data from 17 listed conventional banks between 2010 and 2022, the study compares the impact of Bloomberg’s investor-oriented ESG scores and the Global Reporting Initiative (GRI)’s stakeholder-driven indices. A two-stage least squares (2SLS) estimation is applied to address endogeneity and test the indirect effect of ESG on firm value through CLLP. The findings reveal that GRI-based ESG disclosures—particularly in the social and governance dimensions—exert a consistent and statistically significant indirect effect on firm value through conservative credit provisioning. In contrast, Bloomberg-based ESG scores show weaker or statistically insignificant relationships, indicating limited local relevance. These results validate the mediating role of CLLP and support both signaling and stakeholder theories in explaining the ESG–firm value nexus. The study suggests that adopting context-sensitive ESG standards like GRI can enhance disclosure credibility, strengthen credit risk governance, and improve firm valuation. The findings also have practical implications for regulators aiming to align ESG frameworks with domestic institutional contexts in emerging markets such as Indonesia.